19 Elevated calcium and phosphate impair mitochondrial function in calcifying human vascular smooth muscle cell. Issue 24 (24th November 2011) - Kapustin, A; Galkin, A; Furmanik, M; Alvarez-Hernandez, D; Shanahan, C
Abstract : Background: Vascular calcification is a strong risk factor for cardiovascular morbidities and mortality of patients with chronic kidney disease where the blood levels of calcium (Ca) and phosphate (P) are significantly altered. Calcification is driven by the osteogenic transition of vascular smooth muscle cells (VSMCs) and is accompanied by accumulation of calcium phosphate crystals in the mitochondrial matrix which might alter bioenergetic metabolism. In the present study we examined the effect of elevated calcium and phosphate on VSMC mitochondrial function. Methods: Human VSMCs were incubated in elevated Ca and P conditions for 16 h and mitochondrial respiration was measured using O2 -electrode. A lucigenin chemiluminescence assay was used for superoxide detection. Complex I content and Citrate Synthase activity were detected spectrophotometrically. Results: Elevated Ca and P treatment significantly reduced the oxygen consumption of VSMCs. The mitochondria of VSMCs incubated in control conditions or in the presence of elevated Ca and P demonstrated a high degree of coupling as revealed by oxygen consumption in the presence of the mitochondrial uncoupler. There was only a small reduction in the total number of mitochondria in calcifying conditions as determined by Complex I and Citrate Synthase activity. Loss of mitochondrial activity was accompanied by an increase in superoxide production. Conclusions: Our data show that elevated Ca and P cause mitochondrial damage and increase superoxide production in VSMCs. We hypothesise that impairment of mitochondrial function can dramatically change VSMC metabolism, promote oxidant stress, and, eventually trigger vascular calcification.